The mental health and wellbeing of medical students-A case study reflection - Arunpreet Sahota (Archives of Depression and Anxiety - Peertechz Publications, 2020)
Introduction: Depression is one of the most commonly diagnosed mental disorders among adults, previously seen as an acute and self-limiting illness, but is now recognised as a chronic, lifelong illness. The importance of mental health and wellbeing has been recognised among young adults and moreover healthcare professionals. Interviewing a patient with chronic anxiety and depression, I reflect how these relate to the published literature relating to the metal health and wellbeing of medical students. Methods: Interviewing  a patient suffering with chronic anxiety and depressive illness,  I highlight a number of areas I found thought provoking and review  the published literature relating to mental health and wellbeing of medical students. Results: The prevalence of depression or depressive symptoms in medical students is around  27.2% internationally,  with  suicidal ideation in  approximately  11.1%. The prevalence of anxiety is much higher, 33.8%,  most prevalent among medical students from the Middle East and Asia. Furthermore, medical students have a significantly higher prevalence of anxiety related symptoms compared with other non-medical students. Most worryingly two out of three  medical students with generalised anxiety symptoms and one in two with depressive symptoms do not seek medical or psychological care. Mindfulness-based interventions decrease stress, anxiety, and depression and improve mindfulness, mood, self-efficacy, and empathy in health care students. Discussion: There is a high prevalence of anxiety and depression amongst medical students and in those with anxiety symptoms alone, the risk of developing other mental health symptoms long-term is high. Medical student mental  health and wellbeing has been recognised by the British Medical Association  and proposal to include mental health awareness and promotion of self-care practices as part of the core curriculum. There are many self-help interventions that can help to reduce general anxiety symptoms and medical students should be more encouraged to take part in university societies, and extracurricular activities.